EXPLORING THE IMPACT OF ECONOMIC CRISES ON CONSUMER BANKING BEHAVIOR AND LOAN PERFORMANCE - Zaenal; Ricky Agusiady; Vilma Dewi Anggraeni (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Background:Economic crises fundamentally test the resilience of financial systems and significantly transform consumer banking behavior, triggering shifts in attitudes toward risk, borrowing, and savings. Aims:This study investigates the multifaceted influence of economic crises on consumer banking behavior and loan performance across different crisis scenarios. Research Method:Employing a mixed-methods approach, we analyzed three major crises: the 2008 financial crisis, COVID-19 pandemic, and recent inflationary pressures, using data from banking institutions and in-depth interviews. Results and Conclusion:Default rates increased 35% during crises while new loan originations decreased 42%. Consumer savings increased 28%, indicating flight to safety. Behavioral patterns include delayed purchases, preference for adjustable rates, and increased digital banking reliance. Contribution:This research contributes empirical evidence of behavioral transmission mechanisms during economic shocks, offering strategic insights for adaptive risk management frameworks and customer communication strategies.